Deforestation reduces rainfall and agricultural revenues in the Brazilian Amazon - Argemiro Teixeira Leite-Filho (Nature Portfolio, 2021)
Deforestation in the Amazon region has suggested to influence precipitation in a non-linear way. Here, the authors show that forest loss is associated with decreasing precipitation after a scale-dependent threshold is crossed, which can cause stress on agriculture if deforestation is expanded.